Involvement of alpha(1B)-adrenoceptors in the anti-immobility effect of imipramine in the tail suspension test - Ribeiro, Carlos Alberto S. [UNESP]; Pupo, André S. [UNESP] (Elsevier B.V., 2015)
Imipramine is a tricyclic antidepressant inhibitor of norepinephrine and serotonin neuronal reuptake. The roles of specific alpha(1)-adrenoceptor subtypes that might be targeted by the increased synaptic levels of noradrenaline induced by imipramine are not well understood. This study investigates the alpha(1)-adrenoceptor subtypes involved in the anti-immobility effect of imipramine in the mouse tail suspension test. The antiimmobility effect of imipramine (32 mg/kg, i.p.) was significantly antagonised by the non-subtype-selective alpha(1)-adrenoceptor antagonist prazosin (0.5 and 1.0 mg/kg, i.p.). Neither the selective alpha(1A)-adrenoceptor antagonist 5-methyl-3-[3-[3-[4-[2-(2,2,2,-trifluroethoxy)phenyl]-1-piperazinyl]propyl]-2,4-(1H,3H)-pyrimidineclione (RS-100329, 0.5 and 1.0 mg/kg) nor the selective alpha(1D)-adrenoceptor antagonist 8-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-8-azaspiro[4.5]decane-7,9-dione dihydrochloride, (BMY-7378, up to 1.0 mg/kg, i.p.) affected the anti-immobility effect of imipramine. However, the anti-immobility effect of imipramine was significantly antagonised by the selective alpha(1B)-adrenoceptor antagonist (2S)-4-(4-amino-6,7-dimethoxy-2quinazoliny1)-2-[[(1,1-dimethylethyl)aminolcarbonyl]-1-piperazinecarboxylate (L-765,314). In addition, mice treated only with RS-100329 or BMY-7378, but not with L-765,314, showed reduced immobility times in comparison to mice treated with vehicle. These results indicate that the selective antagonism of alpha(1A)- and alpha(1D)- adrenoceptors results in antidepressant-like effects and that the am-subtype is the main target for the increased levels of noradrenaline caused by imipramine. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Alpha(1)-Adrenoceptors; Alpha(1B)-Adrenoceptor; Tricyclic antidepressants; Imipramine; Tail suspension test